A systematic review of epileptic seizures in adults with subdural haematomas. (February 2017) - Won, Sae-Yeon; Konczalla, Juergen; Dubinski, Daniel; Cattani, Adriano; Cuca, Colleen; Seifert, Volker; Rosenow, Felix; Strzelczyk, Adam; Freiman, Thomas M.
Highlights: Overall incidence of ePTS (lPTS) is 28% (43) in aSDH and 10% (5.3) in cSDH in 2–3 years. Recurrence rate of seizures is higher in patients with late PTS compared to early PTS. There are different risk factors for seizures in a- and cSDH. aSDH: 24 h postoperative GCS < 9, craniotomy, preoperative GCS < 8. cSDH: alcohol abuses, mental change, previous stroke and density of haematoma in CT. Abstract: Background: Posttraumatic epileptic seizures (PTS) are a serious complication in patients with subdural haematoma (SDH). However, to date, several studies have shown discordances about SDH-associated seizures in terms of incidence, risk factors and prophylactic antiepileptic treatment. Objective: The aim of this study was to analyse the incidence, risk factors of PTS and the role of prophylactic antiepileptic treatment in patients with SDH. Data sources: A systematic literature review examining PTS in patients with SDH was performed using PubMed gateway, Cochrane Central Register of Controlled Trials, and Excerpta Medica dataBASE between September 1961 and February 2016. Search terms included subdural haematoma, seizure, epilepsy, prophylactic antiepileptic drugs, anticonvulsive medication, and risk factors. Data selection: Human-based clinical studies focusing on epileptic seizures in patients with SDH. Data extraction and synthesis: PRISMA statements were used for assessing data quality. Two independent reviewers extracted data from included studies and disagreement was solved by consensus. Twenty-four studies were identified for inclusion into the study. Results: Overall incidence of early PTS (ePTS) and late PTS (lPTS)/2 years was 28% and 43% in acute SDH (aSDH) whereas the incidence of e- and lPTS was lower in chronic SDH (cSDH; 5.3% vs. 10%). Overall risk factors for PTS in patients with aSDH were: 24 h postoperative Glasgow Coma Score (GCS) score below 9 (OR 10.5), craniotomy (OR 3.9), preoperative GCS below 8 (OR 3.1). In patients with cSDH the risk factors were alcohol abuse (OR 14.3), change of mental status (OR 7.2), previous stroke (OR 5.3) and density of haematoma in computer tomography (OR 3.8). Age, sex, haematoma size/side and midline shifts were not significant risk factors for PTS in both types of SDH. In prevention of PTS phenytoin and levetiracetam showed similar efficacy (OR 1.3), whereas levetiracetam was associated with significantly lower adverse effects (OR 0.1). Limitations: Most of the studies were of retrospective nature with a small sample size. Due to the inclusion criteria, some studies had to be excluded and that might lead to selection bias. Conclusions: PTS are a serious complication in patients with SDH, particularly in aSDH. The "prophylactic use" of antiepileptic drugs might be beneficial in patients with cumulative risk factors.